Quantitative measurement of blood glucose influenced by multiple factors via photoacoustic technique combined with optimized wavelet neural networks. Issue 3 (7th December 2022) - Ren, Zhong; Liu, Tao; Xiong, Chengxin; Huang, Shuanggen; Zhang, Jia; Peng, Wenping; Wu, Junli; Liang, Gaoqiang; Sun, Bingheng
Abstract: In this work, the photoacoustic (PA) quantitative measurement of blood glucose concentration (BGC) influenced by multiple factors was firstly investigated. A set of PA detection system of blood glucose considering the comprehensive influence of five factors was established. The PA signals and peak‐to‐peak values (PPVs) of 625 rabbit whole blood were obtained under 625 influence combinations. Due to the accurate measurement of BGC limited by the overlap PA signals, wavelet neural network (WNN) was utilized to train the PPVs of blood glucose for 500 rabbit blood. The mean square error (MSE) of BGC for 125 testing blood was approximately 6.5782 mmol/L. To decrease the MSE, the parameters of WNN were optimized by particle swarm optimization (PSO), that is, PSO‐WNN algorithm was employed. Under the optimal parameters, MSE of BGC was decreased to approximately 0.48005 mmol/L. To further improve the prediction accuracy of BGC, an improved nonlinear dynamic inertia weight (NDIW) strategy of PSO was proposed, and compared with other two kinds of dynamic inertia weight strategies. Under the optimal parameters, the MSE of BGC was decreased to approximately 0.2635 mmol/L. The comparison of nine algorithms demonstrate that the PA technique combined with PSO‐WNN and the improved NDIW strategy is significant in the quantitative measurement of blood glucose influenced by multiple factors. Abstract : Clarke's error grid analysis of blood glucose concentration for testing set blood specimens with the comprehensive influence of multiple factors based on PSO‐WNN algorithm with the improved nonlinear dynamic inertia weight strategy